Kolaborasi Mahasiswa dan Masyarakat dalam Pemberdayaan desa Melalui Edukasi, Aksi Lingkungan, dan Peringatan HUT RI Ke-80 - Sri Choiriyati; Fathul amin; Dio riski saputra; Neli Septiawati Agustin; Dea Nurul Falah; Ferti Della Triwinda; Silvia Kartisilawa; Rajudacosta Rajudacosta; Muhammad Nauful Zaky (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Collaboration between students and the community is a crucial strategy in village empowerment to achieve sustainable development. This study aims to describe the forms of student-community collaboration in educational programs, environmental actions, and the commemoration of the 80th Indonesian Independence Day in West Ambarawa Village, Pringsewu Regency. The method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation during program implementation. The results indicate that educational activities, including campus outreach, prevention of immorality, anti-bullying, and early childhood education (PAUD) mentoring, increased educational awareness and social literacy. Environmental actions such as mutual cooperation (gotong royong) and mosque revitalization successfully strengthened the values of mutual cooperation and environmental cleanliness. Furthermore, QRIS socialization positively impacted the digital literacy of MSMEs, while local tourism promotion increased the village's tourism potential. The commemoration of the 80th Indonesian Independence Day served as a platform for strengthening social capital and community togetherness. Despite challenges such as limited time and participation, this collaboration significantly contributed to strengthening community capacity. Further recommendations include ongoing mentoring, infrastructure support, and strengthening the role of youth to ensure the program's sustainability.